2017
DOI: 10.1101/233429
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patchiness and scale-free correlations: characterising criticality in ecosystems

Abstract: A variety of ecosystems exhibit spatial clustering devoid of characteristic sizes, also known as scale-free clustering. In physics, scale-free behaviour is known to arise when a system is at a critical point, which occurs at the edge of two phases of matter. Scale-free clustering in physics therefore indicates that a system is not resilient. Spatial ecological studies, however, posit that scale-free clustering arises away from critical points and is therefore an indicator of robustness. This inconsistency is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 79 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…The sizes and numbers of those patches can be readily quantified from remote-sensing images, and such patterns can be used to infer whether facilitation occurs between plants (Chen et al 2022;Xu et al 2015). This is traditionally done by summarizing the spatial structure into spatial statistics, such as spatial autocorrelation (Sankaran et al 2017) or type of patch size distribution (Kéfi et al 2011;Siteur et al 2023), and linking the observed changes in those metrics to theoretical results (Kéfi et al 2011;Scanlon et al 2007). However, such qualitative comparison logically results in a qualitative and corroborative result, i.e.…”
Section: Inference Of Local Interactions From Landscape-scale Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sizes and numbers of those patches can be readily quantified from remote-sensing images, and such patterns can be used to infer whether facilitation occurs between plants (Chen et al 2022;Xu et al 2015). This is traditionally done by summarizing the spatial structure into spatial statistics, such as spatial autocorrelation (Sankaran et al 2017) or type of patch size distribution (Kéfi et al 2011;Siteur et al 2023), and linking the observed changes in those metrics to theoretical results (Kéfi et al 2011;Scanlon et al 2007). However, such qualitative comparison logically results in a qualitative and corroborative result, i.e.…”
Section: Inference Of Local Interactions From Landscape-scale Patternsmentioning
confidence: 99%
“…2015). This is traditionally done by summarizing the spatial structure into spatial statistics, such as spatial autocorrelation (Sankaran et al . 2017) or type of patch size distribution (Kéfi et al .…”
Section: Introductionmentioning
confidence: 99%
“…a spanning cluster. As density decreases, this spanning cluster breaks down into smaller ones until a barren ecosystem state is reached (Corrado, Cherubini, & Pennetta, ; Kéfi et al., ; Sankaran, Majumder, Viswanathan, & Guttal, ; Van Den Berg, ). When using spatio‐temporal data, this sequential process is reflected in changes of the patch size distribution (PSD) (Kéfi et al., ).…”
Section: The Spatial Ews and Their Expected Trendsmentioning
confidence: 99%
“…(4) In the final stages before reaching a fully empty state, only small patches persist and the patch size distribution is best‐described by an exponential distribution ( e − βx ) with presence of a spanning cluster of empty cells. Identifying where in these four phases an ecological system lies could thus constitute an indicator of degradation level (Kéfi et al., , but see Sankaran, Majumder, Viswanathan, et al., ; Schneider & Kéfi, ).…”
Section: The Spatial Ews and Their Expected Trendsmentioning
confidence: 99%